Le recours en cassation dans le contentieux municipal - Rousseau, Gilles (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1980)
This paper describes the specific nature of proceedings to quash decisions of local authorities under a number of provisions in Québec statutes. Similar provisions exist in the law of other Canadian provinces. Paying relatively scant attention to the historical background of such procedures, the paper highlights the limitations and deficiencies inherent in them. Not all interested parties may bring them ; not all decisions of local authorities may be reviewed in this way ; not all remedies are open to be sought, especially those of a monetary nature; and fairly stringent time-limits apply to them. Taken together, these constraints disclose the true nature of such proceedings : they are an additional safeguard given to ratepayers as specially interested parties, to broaden the access to judicial review of actions by local authorities. These constraints also explain to a large extent why the existence of that additional avenue of recourse has not materially affected the use of general administrative-law remedies, whether direct and offensive such as actions to annul or declarations, or indirect and defensive such as evocation or exception on grounds of illegality.